2021
DOI: 10.3390/ijms22041526
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of the Ubiquitin–Proteasome System in the Endoplasmic Reticulum Stress Pathway

Abstract: The endoplasmic reticulum (ER) is a highly dynamic organelle in eukaryotic cells, which is essential for synthesis, processing, sorting of protein and lipid metabolism. However, the cells activate a defense mechanism called endoplasmic reticulum stress (ER stress) response and initiate unfolded protein response (UPR) as the unfolded proteins exceed the folding capacity of the ER due to the environmental influences or increased protein synthesis. ER stress can mediate many cellular processes, including autophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 171 publications
(200 reference statements)
0
37
0
Order By: Relevance
“…This is believed to occur due to ATF6 activating quickly when compared to IRE1, which has to induce XBP1 splicing and translation of XBP1 to an active protein. During this time, the ER chaperones induced by ATF6 are able to promote protein folding before spliced XBP1 induces ERAD genes which promote the degradation of unfolded proteins [ 63 , 64 ].…”
Section: Erad Inductionmentioning
confidence: 99%
“…This is believed to occur due to ATF6 activating quickly when compared to IRE1, which has to induce XBP1 splicing and translation of XBP1 to an active protein. During this time, the ER chaperones induced by ATF6 are able to promote protein folding before spliced XBP1 induces ERAD genes which promote the degradation of unfolded proteins [ 63 , 64 ].…”
Section: Erad Inductionmentioning
confidence: 99%
“…The signaling of KDEL receptors via G s GPCRs can modulate autophagy [35,36]. Autophagy is essential for the degradation of misfolded proteins and the UPR has been shown to induce autophagy through several pathways [37,38]. Wang et al, 2011, showed that KDEL receptors localize to the lysosomes when overexpressed, which correlated with an increase in autophagy.…”
Section: Kdel Receptor and Autophagymentioning
confidence: 99%
“…A majority of intracellular proteins are modified by ubiquitination ( Amm et al, 2014 ). Several Ub signals are recognized by proteasomes, thereby serving as a regulatory mechanism for protein degradation, affecting nearly all aspects of cellular processes ( Chowdhury and Enenkel, 2015 ; Hanna et al, 2019 ; Sakai et al, 2020 ; Fhu and Ali, 2021 ; Goetzke et al, 2021 ; Qu et al, 2021 ; Zou and Lin, 2021 ). Ubiquitin signaling is strictly regulated by a multistep cascade reaction consisting of three enzyme groups.…”
Section: Introductionmentioning
confidence: 99%